-10j=19-11j

Simple and best practice solution for -10j=19-11j equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10j=19-11j equation:


Simplifying
-10j = 19 + -11j

Solving
-10j = 19 + -11j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '11j' to each side of the equation.
-10j + 11j = 19 + -11j + 11j

Combine like terms: -10j + 11j = 1j
1j = 19 + -11j + 11j

Combine like terms: -11j + 11j = 0
1j = 19 + 0
1j = 19

Divide each side by '1'.
j = 19

Simplifying
j = 19

See similar equations:

| 5n-6=6n+11 | | 2(22-8)=22+6 | | (z^(-1/2)z^(5/2))/(z^(1/3)) | | 10+6-3r=-10+10r | | 12(12k+11)=12(12k+12) | | 6x-35=71 | | 2(y-8)=y+6 | | 2.5=ln(7/x) | | 7=ln(2.5/x) | | 18y^2-37y-20=0 | | 2+.08x=.2x+8 | | Z2/6-7z/2-12=0 | | 6x^2+43x-15=0 | | 6/7z=3 | | 25a^2+25ac-14c^2=0 | | -6.1c=-24.4 | | 3(a+m)+2(b+n)-3a-2b=0 | | 3x-1=6T+2 | | 23x+98=63 | | p-40=24.76 | | h^2+11h+4=0 | | Log(67)=log(21x) | | 3(a+m)+2(b+n)=3a+2b | | -x+12=6 | | -z+2=13 | | 67=21x | | 4n-6-5n=8-n+7 | | 1/2×-2=2-5/3× | | 21xy/20x | | .16x+.6(x-4)=.01(3x-3) | | t-5+6t=3(3t-3) | | -6(4x-4)+8=-24x+32 |

Equations solver categories